Optimal management of young adult transplant recipients: the role of integrated multidisciplinary care and peer support - Paul Neil Harden; Sam Nicholas Sherston (Annals of Saudi Medicine, 2013)
Young adults with chronic diseases do not fit easily into an aging adult patient population and are frequently isolated from peers. The result is a high rate of non-adherence with medical care and therapy, resulting in poor outcomes. This is an important clinical problem shared equally by young adults transitioning from pediatric care and those presenting directly to adult care. An integrated multidisciplinary pediatric–adult service can improve the transition process and preparation of the teenager for adult health care. A seamless transition into a dedicated young adult service results in reduced premature failure rates of kidney transplants and improved clinic and medication adherence.